2023
DOI: 10.23865/nbf.v20.293
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the majority language in Norwegian ECEC: Relating language-learning environment in ECEC to expressive vocabulary

Abstract: Developing proficiency in the language(s) spoken in any given society is crucial for the inclusion and attainment of children in that society. With an enrolment rate in Norwegian early childhood education and care (ECEC) of 93.4% for children between age one and five, ECEC constitutes an important out-of-home learning environment for children in Norway. In this study, we examine how the quality of language-learning environments in toddler and preschool groups predicts children’s expressive vocabulary in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The quality of the language environment in ECEC classrooms has been found to predict monolingual Norwegian children's language skills (Hansen et al, 2023). Several studies have shown that read-aloud activities can provide rich language inputs for young children.…”
Section: Read-alouds As a Literacy Practice For Multilingual Children...mentioning
confidence: 99%
“…The quality of the language environment in ECEC classrooms has been found to predict monolingual Norwegian children's language skills (Hansen et al, 2023). Several studies have shown that read-aloud activities can provide rich language inputs for young children.…”
Section: Read-alouds As a Literacy Practice For Multilingual Children...mentioning
confidence: 99%